Pakistan : Skills Assessment for Economic Growth - World Bank (World Bank, Washington, DC, 2019)
In an era of globalization and rapidly changing technology, the nature of work and skills required is also rapidly changing, and it calls for an urgent need to redefine the types of skills considered in public policy. Technology is reshaping the demand for skills by reducing the value of skills that can be substituted by technologies. Technology is affecting the demand particularly for three types of skills in the workplace. First, the demand for nonroutine cognitive and socio-behavioral skills appear to be rising in both advanced and emerging economies. Second, the demand for routine job-specific skills is declining, and third, the value of combinations of different skill types appear to be increasing. In this context, skills, often used as a synonym for technical and vocational education and training (TVET) in public policy discussions, need to be redefined. The World Bank’s skills toward employment and productivity (STEP) framework defined three types of skills: (a) cognitive skills, (b) socio-behavioral skills, and (c) technical skills. The aim of this report is to discuss how Pakistan should deal with the skills development agenda for competitive economic growth. The study will focus on the big-picture questions of skills demand and supply in Pakistan by assessing the current situations of the skills demands, profiles of existing workers and future labor market entrants, and skills development opportunities in Pakistan and by discussing models and policy options for new skills and human capital development systems in Pakistan.